The Effect of Residual Palladium Catalyst Contamination on the Photocatalytic Hydrogen Evolution Activity of Conjugated Polymers. Issue 34 (16th October 2018) - Kosco, Jan; Sachs, Michael; Godin, Robert; Kirkus, Mindaugas; Francas, Laia; Bidwell, Matthew; Qureshi, Muhammad; Anjum, Dalaver; Durrant, James R.; McCulloch, Iain
Abstract: The effect of residual Pd on hydrogen evolution activity in conjugated polymer photocatalytic systems is systematically investigated using colloidal poly(9, 9‐dioctylfluorene‐alt‐benzothiadiazole) (F8BT) nanoparticles as a model system. Residual Pd, originating from the synthesis of F8BT via Pd catalyzed polycondensation polymerization, is observed in the form of homogeneously distributed Pd nanoparticles within the polymer. Residual Pd is essential for any hydrogen evolution to be observed from this polymer, and very low Pd concentrations (<40 ppm) are sufficient to have a significant effect on the hydrogen evolution reaction (HER) rate. The HER rate increases linearly with increasing Pd concentration from <1 ppm to approximately 100 ppm, at which point the rate begins to saturate. Transient absorption spectroscopy experiments support these conclusions, and suggest that residual Pd mediates electron transfer from the F8BT nanoparticles to protons in the aqueous medium. Abstract : Residual Pd in organic semiconductor nanoparticles is essential for their photocatalytic activity . The cross‐coupling catalyst Pd2 (dba)3 used in conjugated polymer synthesis decomposes to form Pd nanoparticles within the polymer. These act as a hydrogen evolution co‐catalyst, which enables electron transfer from the polymer to the surrounding aqueous protons.